Pectin fractions extracted sequentially from Cerasus humilis: their compositions, structures, functional properties and antioxidant activities - Shikai Zhang; Geoffrey I.N. Waterhouse; Tingting Cui; Dongxiao Sun-Waterhouse; Peng Wu (Food Science and Human Wellness)
Three pectin fractions (water-soluble fraction (WSF), chelator-soluble fraction (CSF), and sodium carbonate-soluble fraction (NSF)) were obtained from Chinese dwarf cherry (Cerasus humilis) fruits. All of them were branched low methoxylated pectins with an amorphous or partially nanocrystalline nature and eight neutral monosaccharides (arabinose and galactose were most abundant). WSF, CSF and NSF had a degree of methylation (DM) of 35.82 %, 14.85 % and 7.13 %, uronic acid (UA) content of 76.02 %, 83.71 % and 69.01 %, and total protein content of 2.4 %, 2.1 % and 8.8 %, respectively. Their molecular weights were 340.31, 330.16 and 141.31 kg/mol, respectively (analyzed by gel permeation chromatography (GPC)). WSF, CSF and NSF exhibited good rheological, thermal, emulsifying, emulsion-stabilizing, water-adsorbing, oil-binding, cholesterol-binding and antioxidant properties. NSF had the highest emulsifying, emulsion stabilizing, water-/oil-/cholesterol-binding and antioxidant capacities, followed by CSF. NSF had the highest viscosity (406.77 mPa·s), flowability, and resistance to heat-induced changes/damage, which may be related to its lowest polydispersity index, DM and UA content and highest protein content. The three pectin fractions with desirable characteristics can be used as food additives/ingredients and dietary supplements.